Analisis Faktor-Faktor Penentu Minat Beli Produk “Sejauh Mata Memandang - Oka Putri, Ni Putu Dian; Dewi, Putu Purnama (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to examine the influence of green marketing, brand image, and environmental knowledge on purchase intention. The research employed a quantitative survey method distributing online questionnaries to 150 respondents who follow the Instagram account @sejauh_mata_memandang and are familiar with Sejauh Mata Memandang’s products. The collected data were analyzed using SmartPLS. The result show that green marketing and brand image have a positive and significant effect on both purchase intention and environmental knowledge. Furthermore, environmental knowledge has a positive influence on purchase intention and serve as a mediating variable that strengthens the relationship between green marketing and brand image with purchase intention. The research model explains 52,1% of the variance in the endogenous variable. These findings indicate that consistant green marketing strategies and brand image emphasizing sustainability values can enhance consumers’ environmental awareness. This knowledge ultimately encourages positive attitudes and purchasing decisions toward eco-friendly products. The practical implication of this research highlights the importance of integrating sustainability values into marketing strategies to foster consumer loyalty and increase purchase intention toward sustainable products.